Audit of Clinical Profile and Outcomes of Acute Variceal Bleed in a Tertiary Care Hospital - Anurag Lavekar; Vijaykumar TR; Nandeesh HP; Deepak Suvarna; Aradya HV; Ritesh Reddy (Journal of Digestive Endoscopy, 2019)
Aims The main purpose of this article is to conduct audit of clinical profile and outcomes of patients presenting with acute variceal bleed in a tertiary care hospital. Methods and Material This was a retrospective study of patients presenting with variceal bleed in a tertiary care center. Data were generated through a computerized electronic record system. Data of patients admitted for acute variceal bleed from August 2018 to December 2018 were collected and considered for analysis. Statistical analysis was done using the software Statistical Package for the Social Sciences (SPSS) 22.0 version. Results Overall, 107 cases were analyzed. In 89.7% (96) cases, cirrhosis of liver was a cause of variceal bleed. Besides, 77.6% (83) patients had large esophageal varices. Five patients (4.7%) required glue injection. Rebleed rate in present study was 0.9%. Mortality due to variceal bleed was 9.3% (10). Acute rebleed (p = 0.002), low mean arterial pressure (MAP; p = 0.001), low platelet count (p = 0.001), high serum creatinine (p = 0.001), high serum total bilirubin (p = 0.001), high international normalized ratio (INR; p = 0.001), and higher model for end stage liver disease (p = 0.001) were associated with increased risk of mortality. Door to endoscopy time (<12 hours or 12–24 hours) did not affect the mortality rate (p = 0.699). Terlipressin given 24 hours after endotherapy is equally effective as terlipressin given 5 days after endotherapy. Conclusion Mortality due to acute variceal bleed can be reduced with timely intervention. Low MAP, low platelet count, higher serum bilirubin and creatinine, and higher INR are predictors of increased mortality due to variceal bleed. Endoscopy done within 12 to 24 hours of presentation did not affect the outcome.